Measurable bundles of C*-dynamical systems - Ganiev, Inomjon; Mukhamedov, Farrukh (Universiti Teknologi MARA, Negeri Sembilan, 2011)
In the present paper we investigate L -valued states and Markov operators on C* -algebras over L . In particular, we give representations for L -valued state and Markov operators on C*- algebras over L , respectively, as measurable bundles of states and Markov operators. Moreover, we apply the obtained representations to study certain ergodic properties of C*-dynamical systems over L .